2017
DOI: 10.1016/j.atherosclerosis.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Screening of circulating microRNA biomarkers for prevalence of abdominal aortic aneurysm and aneurysm growth

Abstract: This large cohort study identified several novel miRs with altered expression in AAA patients when compared to controls. Assessment of miR expression may offer an opportunity to predict disease progression and aneurysm growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 21 publications
2
44
0
Order By: Relevance
“…No such differences were measured with the following genes: IL‐6 (n=466)31; Cystatin C (n=412)83; OPN (n=198)84; and 9p21 (n=741) 85. Of 20 investigated genetic markers, 10 were investigated by Wanhainen et al86 in 169 follow‐up patients (all concerning microRNA as marker for expansion), of which 8 markers demonstrated significant differences between slow and fast growing AAA.…”
Section: Resultsmentioning
confidence: 99%
“…No such differences were measured with the following genes: IL‐6 (n=466)31; Cystatin C (n=412)83; OPN (n=198)84; and 9p21 (n=741) 85. Of 20 investigated genetic markers, 10 were investigated by Wanhainen et al86 in 169 follow‐up patients (all concerning microRNA as marker for expansion), of which 8 markers demonstrated significant differences between slow and fast growing AAA.…”
Section: Resultsmentioning
confidence: 99%
“…Aortic aneurysm (AA) is an increasingly common and ultimately fatal rupture with no effective drug treatment, 187 are decreased. 191,193 However, miR-29b was up-regulated in human tissues from thoracic AA patients. 187 Moreover, serum miR-29c-3p…”
Section: Aneurysmmentioning
confidence: 96%
“…MiR‐24 is significantly decreased in both tissue and plasma of AAA patients and is inversely related to the size of the AAA 192. Recently, miR‐33a‐5p, let‐7i‐5, miR‐652‐3p and miR‐331‐3p are elevated in plasma of AAA patients compared with healthy controls, and miR‐192‐5p, miR‐10b‐5p, miR‐194‐5p, miR‐215‐5p, miR‐205‐5p, miR‐16‐5p, miR‐126, miR‐124a, miR‐155, miR‐223, miR‐29b, miR‐15a and miR‐15b are decreased 191, 193. However, miR‐29b was up‐regulated in human tissues from thoracic AA patients 187.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 99%
“…However, aberrant expression of siRNA and miRNA also contributes to initiation and progression of AAA, and several studies reported that miRNA might be available as a biomarker to predispose AAA formation. 28) Therefore, a role of these molecules in the process Molecular Pharmacological Approach for Aneurysm of AAA formation has gained research interest, and modulation of their expression has been investigated in several experimental studies. siRNA and miRNA are a class of non-coding doublestranded RNA and induce posttranscriptional gene silencing in a sequence-specific fashion.…”
Section: Small Interfering Rna and Micrornamentioning
confidence: 99%